The Euro as Legal Tender : A Comparative Approach to a Uniform Concept - Freitag, Robert; Omlor, Sebastian (De Gruyter, 2020)
Twenty years following the introduction of the euro as single European currency, it remains unclear whether Article 128 of the TFEU enshrines an autonomous concept of legal tender with regard to the euro or whether the provision merely refers to pre-existing concepts of legal tender in the national laws of member states. This work collects all contributions to the 2018 conference "The Euro as Legal Tender" held in Frankfurt-am-Main.